2010
DOI: 10.1007/s11481-010-9248-1
|View full text |Cite
|
Sign up to set email alerts
|

Glatiramer Acetate Modulates TNF-α and IL-10 Secretion in Microglia and Promotes Their Phagocytic Activity

Abstract: Glatiramer acetate (GA) is an approved immunomodulating agent for the treatment of relapsing-remitting multiple sclerosis. Its mode of action is attributed to a T helper cell-type 1 (Th1) to Th2 cytokine shift in T cells. Th2-type GA-reactive T cells migrate into the brain and act suppressive at the sites of inflammation. However, there is increasing evidence that the effect of GA is not confined to T cells. It inhibits broadly the activation of monocytes and induces peritoneal macrophages and monocytes to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 41 publications
3
43
0
Order By: Relevance
“…Recently, we demonstrated that GA drives microglia to adopt a type II APC similar to monocytes and DCs suggesting a general effect on myelo-monocytic cells [16]. We additionally discovered that GA directly and distinctly increases phagocytic activity of primary rat microglia.…”
Section: Introductionmentioning
confidence: 79%
“…Recently, we demonstrated that GA drives microglia to adopt a type II APC similar to monocytes and DCs suggesting a general effect on myelo-monocytic cells [16]. We additionally discovered that GA directly and distinctly increases phagocytic activity of primary rat microglia.…”
Section: Introductionmentioning
confidence: 79%
“…Since microglia have been recognized as an important contributor to tissue damage and disease progression in MS [10], it is possible that part of the beneficial effect of glatiramer acetate in MS is derived from an effect on microglia. Indeed, glatiramer acetate has been found to have direct effects on microglia, promoting differentiation of monocytes and microglia into antigen-presenting cells [28] and stimulating phagocytosis by microglia in vitro [29]. …”
Section: Discussionmentioning
confidence: 99%
“…The production of IL-10 by microglia can also be induced in a PRR-independent manner. Glatiramer acetate, an immunomodulatory agent used in relapsing-remitting multiple sclerosis, was shown to induce secretion of IL-10 by microglial cells [95]. Resveratrol administration to a microglial cell line prevented hypoxia-induced injury by up-regulating IL-10 and controlling inflammation [96].…”
Section: Cellular Sources Of Il-10 In the Cnsmentioning
confidence: 99%